2022
DOI: 10.1002/ldr.4519
|View full text |Cite
|
Sign up to set email alerts
|

Elevated salinity decreases soil ecosystem multifunctionality by shifting the bacterial community from K‐ to r‐selected living strategy

Abstract: Deciphering ecosystem multifunctionality (EMF) driven by abiotic and biotic factors is crucial for evaluating soil nutrient cycling and retention. Yet, there is little information on whether microbial r/K-selection can play the same role as community diversity to reflect EMF. Using Illumina MiSeq sequencing, phospholipid fatty acid (PLFA) technique, and multiple statistical analyses, we estimated linkages among salinity, soil EMF, community diversities, microbial r/K-selection, and bacterial ecological assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…We also observed that soil G + / G − ratio, a proxy for microbial k-strategists, significantly increased under Low N and Moderate N, but did not change under High N treatments (Figure 2d). Other studies observed a similar soil microbial composition transition under different environmental pressures, for example, elevated soil salinity and increased atmospheric CO 2 (Cheng & Wan, 2023;Sun et al, 2021). In fact, k-strategists in mature forest soils play an important role in utilizing recalcitrant organic matter (Zhu et al, 2022).…”
Section: Factors Driving Soil P Transformation After 18year Long-term...mentioning
confidence: 72%
“…We also observed that soil G + / G − ratio, a proxy for microbial k-strategists, significantly increased under Low N and Moderate N, but did not change under High N treatments (Figure 2d). Other studies observed a similar soil microbial composition transition under different environmental pressures, for example, elevated soil salinity and increased atmospheric CO 2 (Cheng & Wan, 2023;Sun et al, 2021). In fact, k-strategists in mature forest soils play an important role in utilizing recalcitrant organic matter (Zhu et al, 2022).…”
Section: Factors Driving Soil P Transformation After 18year Long-term...mentioning
confidence: 72%